Distribution, introduction pathway, and invasion risk analysis of the North American crayfish Procambarus clarkii (Decapoda: Cambaridae) in southeast Brazil - Loureiro, Tainã G. (2015)
This study reports new records of Procambarus clarkii Girard, 1852 in Southeastern Brazil and investigates its possible pathways of introduction. The Brazilian crayfish pet trade was surveyed with regard to species’ availability and price, reporting its persistence, even though illegal. An invasion risk analysis was performed by applying a protocol developed specifically to invasive freshwater invertebrates (FI-ISK). Procambarus clarkii has confirmed occurrences from urban and non-urban areas in the state of São Paulo, including the Jaraguá State Park, an Atlantic Forest conservation area. The pet trade is an important introduction vector but some subsequent translocation can also be due to the release of live bait by anglers. Besides passive dispersal, these newly discovered populations, especially those located in non-urban areas, are likely to naturally disperse further through active spread and river drift of juveniles. Although confirmed colonized areas are all located in the state of São Paulo, the invasive risk analysis showed that P. clarkii is a potential highly invasive species for Brazil. These introductions have unknown consequences; however, many impacts are associated with this species establishment around the world, underlining the urgency to understand the invasion process in Brazil and develop efficient management techniques.